The identity to prove is `(sin^2 x)/(1-cos x)= (sec x+1)/sec x`

`(sin^2x)/(1-cos x)`

=> `(1 - cos^2x)/(1 - cos x)`

=> `((1 + cos x)(1 - cos x))/(1 - cos x)`

=> `(1 + cos x)`

=> `(1 + 1/sec x)`

=> `(sec x + 1)/sec x`

**This proves that** `(sin^2x)/(1-cosx)=(secx+1)/secx`

## We’ll help your grades soar

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now